Changes in Problematic Mealtime behaviors among 3- to 6-Year-Old Children Following Sapere-Based Sensory Education: A Pre-Post Intervention Study - Kawaguchi, Yaeko; Somei, Junichiro; Domichi, Masayuki; Suganuma, Akiko; Sakane, Naoki (International Journal of Child Health and Nutrition, 2026)
Introduction: Feeding difficulties are commonly observed in children, especially those with developmental concerns. This study aimed to evaluate the effects of Sapere-based sensory education on mealtime behavior and food acceptance in preschool-aged children using a pre-post intervention design. Methods: A quasi-experimental, multi-site prospective study was conducted with 148 children aged 3 to 6 years. Participants were divided into two groups: 74 children with problematic mealtime behavior (PMB), assessed using the ASD-Mealtime Behavior Questionnaire, and74 age- and sex-matched non-PMB in contrast. Food pickiness and neophobia were evaluated using a validated food rejection scale. The intervention consisted of sensory-based dietary education using the Sapere method, with assessments conducted before and six months after the intervention. Results: Significant improvements were observed in the PMB group following the intervention. Specifically, reductions were observed in clumsiness/manners (–4.2 ± 0.8, p < 0.001), interest/concentration during eating (–1.7 ± 0.7, p = 0.014), and oral motor function difficulties (–1.0 ± 0.5, p = 0.039). Food pickiness also showed a significant decrease (–1.4 ± 0.4, p =0.002). Although selective eating and food neophobia showed downward trends, the changes were not statistically significant. In contrast, no significant changes were noted in the non-PMB group for any behavioral or food rejection measures. Conclusion: Sapere-based sensory education may effectively reduce problematic mealtime behaviors and food pickiness among preschool-aged children. These findings support the potential utility of sensory-based interventions for promoting healthy eating behaviors in early childhood.